Slowdown in the Decay of Western North Pacific Tropical Cyclones Making Landfall on the Asian Continent - Song, Jinjie; Klotzbach, Philip J.; Zhao, Haikun; Duan, Yihong (Frontiers in Earth Science, 2021)
This study finds an increasing trend in the decay timescale (τ) of western North Pacific (WNP) tropical cyclone (TCs) making landfall on the Asian continent from 1966-2018. Statistical analysis of individual landfalling TCs shows that τ is significantly positively linked to soil wetness, 850-hPa relative vorticity and 200-hPa divergence, whereas it is weakly correlated with 700-500-hPa relative humidity and 850-200-hPa vertical wind shear. For TCs hitting southeastern China, the observed increasing τ is likely caused by enhanced 850-hPa vorticity and 200-hPa divergence. For TCs hitting southern China, increasing τ is likely driven by increased 850-hPa vorticity. By comparison, there are no significant trends in environmental variables over the eastern Indo-China Peninsula, and τ has not significantly changed in this region. Our results imply that the increasing τ of WNP landfalling TCs on the Asian continent are more likely caused by changes in dynamic variables than changes in thermodynamic variables.